The Effect of STAT3 Signal Pathway Activation on Retinopathy of Prematurity - Ren, Jianbing; Jiang, Jingbo; Ou, Weiming; Luo, Xianqiong; Xiang, Jianwen; Liu, Guosheng; Huang, Shuiqing; He, Longkai; Gan, Jiamin; Li, Hongping; Nie, Chuan (Frontiers in Pediatrics, 2021)
Objective: To investigate the mechanism of activation of the signal transducer and activator of transcription 3 (STAT3) signal pathway in the process of retinopathy of prematurity (ROP). Methods: Sixty newborn Sprague-Dawley (SD) rats were randomly separated into the hyperoxia and air control groups (n = 30/in each group). The serum hepcidin level on 21 d was measured using the enzyme-linked immunosorbent assay (ELISA). The expression of HAMP and STAT3 protein in the liver was determined using reverse transcription-polymerase chain reaction (RT-PCR) and western blotting. Retinal neovasculature was evaluated by hematoxylin and eosin (HE) stain and fluorescein lectin. The retinal endothelial cells were treated with 250 μmol/L cobalt chloride for 72 h and added S3I-201. The STAT3 level was determined by western blotting. Results: The expression of STAT3 protein increased significantly after hyperoxia stimulation. The expression of HAMP mRNA in the hyperoxia group was significantly higher than that of the control group. The proliferation of retinal cells was inhibited, and the expression of STAT3 was increased. No significant difference was noted in vascular endothelial growth factor (VEGF) mRNA. The expression of STAT3 and VEGF mRNA was significantly reduced. Conclusion: The activation of the STAT3 signal pathway increased hepcidin expression, contributing to the pathogenesis of ROP. S3I-201 inhibited the expression of STAT3 and VEGF mRNA levels. This information provides potential novel therapeutic approach to the prevention and treatment of ROP.